Identification of elastic - plastic deformation for different degrees of deformation for forming sheet metal by swivel bending - Moravec, J. (Problems of Tribology, 2014)
The thesis deals with the issue of bending. The practical part is dealing with developing of design of bending tool for bending of metal sheet parts and made technological processes for manufacturing of non-standard components.